2018
DOI: 10.1017/s2071832200023361
|View full text |Cite
|
Sign up to set email alerts
|

The Motivations of Individual Judges and How They Act as a Group

Abstract: States have a significant influence on the selection of judges to international courts. This raises the concern that judges will be biased in favor of their home states, a concern backed by some empirical research. To counter that danger, international courts usually sit in large and diverse panels. Scholars have argued that this gives judges only rare occasions to tip the balance in favor of their home states. The problem begins, however, when judges start forming coalitions among themselves, giving judges wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…It is also assumed that judges will be politically unmotivated. However, in the literature we find research on the national systematic bias of judges due to certain factors: psychological (patriotic beliefs); economic (expected material reward); selection conditions (adherence to a certain ideology); cultural (education, experience gained in the country) (Dothan, 2018). At the same time, it seems that it would be possible to avoid a biased interpretation due to the careful formation of the composition of judges for consideration of cases.…”
Section: Svitlana Karvatska Mariia Blikhar Y Nataliia Huralenko Evolmentioning
confidence: 98%
See 2 more Smart Citations
“…It is also assumed that judges will be politically unmotivated. However, in the literature we find research on the national systematic bias of judges due to certain factors: psychological (patriotic beliefs); economic (expected material reward); selection conditions (adherence to a certain ideology); cultural (education, experience gained in the country) (Dothan, 2018). At the same time, it seems that it would be possible to avoid a biased interpretation due to the careful formation of the composition of judges for consideration of cases.…”
Section: Svitlana Karvatska Mariia Blikhar Y Nataliia Huralenko Evolmentioning
confidence: 98%
“…W. Marshall (2002) identifies features of judicial activism. Dothan (2018) explores factors and causes of national systematic bias of judges. Evseev (2015), sharing the position of the retired ECtHR judge A. Kovler, notes that judicial activism occurs when the Court has several interpretations within its case law, but the Court goes beyond that.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Scholars who have examined the national biases of judges in international courts have suggested that, just as in domestic courts, judges may be attitudinal 105 and that similar phenomena (such as small-group dynamics) 106 or patterns of leadership (such as the role of court presidents) 107 may play an important role in shaping collective decisions. 108 Thus, we recommend the following optimal configuration for interpreting in the judicial deliberation procedure: wherever possible, it should seek to support all-things-considered judgements in a genuinely psychologically safe environment of judicial deliberation in which all decisionmaking is based on the conscious weighting of values and follows a two-step process. The first step would involve identifying the type of pragmatic meaning in accordance with the pragmatic typology developed by theoretical research.…”
Section: Second Conclusion: Morally International Lawyers Are Humans Toomentioning
confidence: 99%
“…Second, the question about the determinants of cross-citations contributes to the wider debate about the role of legal and nonlegal factors in judicial decision-making (for a review of this literature, see Dothan 2018Dothan , 2172. These two groups of explanations also reflect the main positions in the general debate about the relationship between law and society.…”
Section: Main Research Question and Wider Implicationsmentioning
confidence: 99%